The impact of metabolic syndrome on the clinical profile and tumor characteristics of endometrial carcinoma - Tawfik, Tawfik A.; Elsabaa, Bassma M.; El-Neily, Dalia A.; El-Tawab, Sally S.; Ebrahim, Heba A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective is to study the influence of different components of metabolic syndrome on clinical behavior and tumor characteristics of endometrial cancer cases and to evaluate if metformin usage affects the stage and grade of endometrial cancer. Methods: 60 women attending the gynecological oncology clinic at El Shatby Maternity University Hospital, after being diagnosed as endometrial carcinoma, were recruited in the study. Serum samples were collected to detect insulin level and lipid profile, and then allocated into two groups according to metabolic syndrome existence. After the recommended surgery, and the routine histopathological diagnosis followed by histopathological chemilumeniscence technique to detect staining intensity, percentage of estrogen receptors ER, and score out of 8 according to Allred score. Results: Endometrial cancer EC patients with metabolic syndrome had a significantly higher age, higher FIGO stages, and higher grade compared to EC without metabolic syndrome (p˂0.05). There was no statically significant difference between both groups in estrogen receptors scoring. HDL was an important factor affecting grade of EC patients, as when HDL decreased by one mg/dl, the grade increased by 0.033% (P=0.030, OR=0.899, OR adjusted=0.826), Insulin level was found to be an important factor affecting stage as when insulin level increased by one Uiu/ml, the stage increased by1.091% (p=<0.001, OR=1.064, OR adjusted=1.091). Conclusions: Hyperinsulinemia was the most important factor affecting aggressiveness of the tumor as regards stage and risk group classification. Metformin failed to show a protective effect against endometrial cancer progression.